CO Oxidation: Flexible Ru/Graphene Aerogel with Switchable Surface Chemistry: Highly Efficient Catalyst for Room‐Temperature CO Oxidation (Adv. Mater. Interfaces 10/2016). Issue 10 (May 2016) - Li, Wencheng; Zhang, Huanhuan; Wang, Jitong; Qiao, Wenming; Ling, Licheng; Long, Donghui
Abstract : Functionalization of 3D graphene aerogels generally requires the drawbacks of pure graphene in the specific desired functionality, which are presently attracting immense research interest on the global level, to be offset. In article 1500711, W. C. Li and co‐workers present the preparation of macroscopic 3D free‐standing Ru nanoparticle/graphene aerogel for room‐temperature CO oxidation. It is found that mild air pretreatment can switch the surface chemistry of nanocrystalline Ru, inducing the formation of highly active oxygen‐vacancy RuOx. This finding may provide an effective guideline for the creation of low‐temperature Ru‐based CO catalysts by optimizing pretreatment conditions.